Aborsi Janin Down Syndrome Dalam Perspektif Maqashid Syariah - Fauzan, Ahmad; Iwan, Iwan (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2025)
This study aims to analyze the legality of abortion for fetuses diagnosed with Down Syndrome from the perspective of Maqasid Sharia. The research method used is normative research with a literature study approach, collecting and analyzing Islamic legal sources, scholars' fatwas, and medical research findings. The results show that, according to the majority of scholars, abortion is prohibited after the fetus reaches 120 days as it is believed that the soul has been breathed into it. However, before this period, opinions among Islamic schools of thought vary; some allow abortion under urgent necessity (darurah) or compelling need (hajat), while others strictly prohibit it. In conclusion, from the Maqasid Sharia perspective, the legality of aborting a fetus with Down Syndrome must consider the principles of protecting life (hifdz an-nafs) and lineage (hifdz an-nasl). Therefore, decisions regarding abortion should be based on the principle of public interest (maslahah), taking into account the mother's and fetus's condition and medical recommendations. Keywords: Abortion, Down Syndrome, Maqasid Sharia.